Upaya Pemasaran Dalam Memperkenalkan Produk Motor Listrik Kepada Masyarakat Di PT The Agung Pamungkas - Farhan Erlianto Ramizzah; Muhammad Ahmi Husein (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
This study aims to analyze the marketing strategy implemented by PT The Agung Pamungkas in introducing Tangkas Motor Listrik products to the public. The research method used is descriptive with a qualitative approach through observation, documentation, and direct interaction with consumers. The marketing strategies implemented include social media branding through content capture and feeds, event booths, and canvassing and flayering activities. The results of the study indicate that social media is effective in increasing brand awareness through creative content and active interaction with consumers. Event booths help people get to know the product directly through consultations and test rides, while canvassing and flayering expand the dissemination of product information. The combination of digital marketing and direct marketing is considered capable of increasing public interest, building an environmentally friendly product image, and supporting increased sales of Tangkas Motor Listrik.